Penyegaran Kemampuan Guru dalam Mengembangkan Media Evaluasi Berbasis IT dengan Berbantuan Software Lectora Inspire - Albrian Fiky Prakoso; Yoyok Soesatyo; Waspodo Tjipto Subroto; Heni Purwa Pamungkas (Jurnal Pengabdian Pada Masyarakat, 2020)
UPGRADING TEACHERS’ ABILITY IN DEVELOPING IT-BASED EVALUATION MEDIA WITH LECTORA INSPIRE-ASSISTED SOFTWARE. Learning assesment take the main role in learning process. Thus, teachers should be able to design a good assessment. However, most of teachers in Magetan have limited knowledge about development learning assessment. Moreover, they need accompaniment to help them to develop learning assessment. This community service aims to (1) give knowledge about learning media, (2) give knowledge about learning assessment, (3) accompany teachers to develop learning assessment using software lectora inspire. The subject for this community service are Economics teachers and Accountant teachers in Magetan. In general, there are two main activities in this community service, namely: seminar (focused on explanation about learning media and assessment theory), and practice to design learning assessment using software lectora inspire. The result of this activity require that most of participant can create their assessment through lectora inspire software.